2021
DOI: 10.3390/agronomy11020254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Plasma Water and Biostimulant on Lawn Functional Value

Abstract: The research was conducted between 2014 and 2016 at the Agricultural Experimental Station of the University of Environmental and Life Sciences in Wrocław. In the experiment, Poa pratensis and Lolium perenne in pure stand and in mixtures were used as Factor A. Two substances that stimulate grass growth and development constituted Factor B. The first was a biostimulant produced from brown algae (Phaeophyceae), containing various essential chemical compounds including amino acids, vitamins, alginic acid, microele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…In the context of decomposition of grass clippings left on the soil, it has been shown that their decomposition occurs most quickly in high air humidity and temperature up to 10°C, beyond which the decomposition rate decreases, which may explain a slight decrease in the OM content 44 . However, it is worth adding that this temperature is exceeded in most months of the grass growing season in Polish climate conditions, hence the experiment was carried out at a constant temperature of 20°C 57 . In addition, because the process provided optimal conditions with regard to the O 2 content, the pH of grass clippings increased due to decomposition, as is the case with composting 58-60 .…”
Section: Grass Clippings Propertiesmentioning
confidence: 99%
“…In the context of decomposition of grass clippings left on the soil, it has been shown that their decomposition occurs most quickly in high air humidity and temperature up to 10°C, beyond which the decomposition rate decreases, which may explain a slight decrease in the OM content 44 . However, it is worth adding that this temperature is exceeded in most months of the grass growing season in Polish climate conditions, hence the experiment was carried out at a constant temperature of 20°C 57 . In addition, because the process provided optimal conditions with regard to the O 2 content, the pH of grass clippings increased due to decomposition, as is the case with composting 58-60 .…”
Section: Grass Clippings Propertiesmentioning
confidence: 99%
“…The application of PAW and the biostimulator [160] decreased the incidence of fungal diseases on the lawn, positively influenced turf density, led to a thicker and more lush lawn, and positively affected overwintering.…”
Section: Spark and Glow Dischargesmentioning
confidence: 99%
“…Humic and fulvic acids tall fescue positive effects observed on transplanted tall fescue, improved quality and heat resistance [124,125] Humic and fulvic acids creeping bentgrass improved root growth at both low and higher fertiliser levels, increased photosynthetic rates and root mass regrowth, improved tolerance to heat and moisture stress, enhanced turfgrass quality [126][127][128] Humic and fulvic acids perennial ryegrass increased uptake of nutrients, promotion of root growth, improved drought tolerance, particularly concerning iron content [36,123,129,130] Humic and fulvic acids Kentucky bluegrass increased root mass and resistance [131] Seaweed extracts Kentucky bluegrass and tall fescue no significant influence on NDVI in frequently mowed turfgrasses [132] Seaweed extracts creeping bentgrass improved visual quality, enhanced shoot and root growth, mitigated summer decline in creeping bentgrass growth [42] Seaweed extracts perennial ryegrass, Kentucky bluegrass decreased prevalence of fungal diseases, increased turf density [133] Protein hydrolysates and free amino acid perennial ryegrass, Kentucky bluegrass, tall fescue improved appearance, functionality, disease resistance, increased nutrient content (N, K, Mg, Na, Mn) [47] Protein hydrolysates and free amino acid creeping bentgrass stimulated N and K uptake, increased grass quality, more shoots, longer roots, increased shoot number, absorbed glutamate for GABA and proline production [134,135] Fungi perennial ryegrass.…”
Section: Biostimulant Plant Species Effect Referencesmentioning
confidence: 99%
“…The study demonstrated that properly applied biostimulants can improve the summer performance of creeping bentgrass. In the work of Talar-Krasa [133], Bio-Algeen S90 significantly decreased the prevalence of fungal diseases in perennial ryegrass and Kentucky bluegrass and increased turf density.…”
Section: Seaweed Extractsmentioning
confidence: 99%